Breaking the News: Parents' Experiences of Receiving an Antenatal Diagnosis of Cleft Lip. (October 2019) - Stock, Nicola Marie; Costa, Bruna; Williams, Jennifer R.; Martindale, Anna; ,
Objective: In high-income countries, many cases of cleft lip are now identified at the 18- to 21-week pregnancy scan. The manner in which a diagnosis is communicated is vital for long-term parental well-being, yet previous studies have been indicative of parental dissatisfaction. The aims of the present study were to examine the experiences of parents who received an antenatal diagnosis of cleft lip in their unborn child and to offer pragmatic suggestions for improving the diagnostic experience in practice. Design: An online, mixed-methods survey was designed and distributed by the Cleft Lip and Palate Association. Data from 574 eligible parents were analyzed using descriptive statistics and inductive content analysis. Results: Although survey responses indicated positive diagnostic experiences overall, respondents perceived a lack of sensitivity among sonographers, long waiting times between referrals, and a lack of appropriate and reliable information. Respondents also reported a number of misconceptions about cleft lip and/or palate and its prognosis, as well as a variety of initial concerns about their own ability to cope with the anticipated challenges. Conclusion: Findings emphasize the importance of providing accurate and individualized information to prospective parents, in a sensitive manner, so they can adjust to their child's diagnosis and prepare for the birth appropriately. Given that antenatal screening for cleft lip is becoming more fully integrated into routine practice, more training for health-care professionals, improved access to reliable information in a variety of formats, and stronger links between local hospitals and specialist cleft services may be needed.